Tinjauan Sistem Desain Pemanfaatan Air Hujan pada Rumah Tinggal di Bintaro, Jakarta - Renhata Katili (Bina Nusantara University, 2012)
Rainwater harvesting and collecting for household domestic needs is someting commonly found. Even in some countries in Africa and Asia,it has been known for a long time. Currently, the technology varies from the simple one like using a barrel up to the purification technology. Unfortunately the rainwater harvesting system commonly found now is rarely integrated as a planned building element. Indeed, the integration will bring good impact on both design and function. This article analyzes a two-story residential building that uses Rainwater harvesting and collecting system which is located in Bintaro, Jakarta, as one example of a planned architecture that uses the system.